2023
DOI: 10.1002/aenm.202302029
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling High Reproducibility and Broad Composition Tolerance in High‐Efficiency Organic Solar Cells via Sequential Deposition

Ruohua Gui,
Kaihu Xian,
Yu Shi
et al.

Abstract: The reproducibility issue is impeding the progress of commercialization in organic photovoltaic (OPV) devices, as the difficulty in precise micro‐nano structure control in bulk heterojunction films, as well as the ineluctable fluctuations of molecular weight and polydispersity index in the synthetic process. Due to such intrinsic properties, the poor regioregularity significantly affects the batch‐to‐batch variation in performance of large‐area or integrative scattered OPV devices. Seeking alternatives as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The LbL active layers suffered from soft plasma peeling off by oxygen glow discharge. The FLAS characterization was performed to explore the component variation in LbL film dependence on the peeling time, 57,58 as displayed in Fig. 7a–c.…”
Section: Resultsmentioning
confidence: 99%
“…The LbL active layers suffered from soft plasma peeling off by oxygen glow discharge. The FLAS characterization was performed to explore the component variation in LbL film dependence on the peeling time, 57,58 as displayed in Fig. 7a–c.…”
Section: Resultsmentioning
confidence: 99%
“…[26,27] Various recent works reported that the film formation kinetics would be significantly affected by device fabrication conditions, such as the processing solvents, the introduction of solid additives, and the processing temperatures. [28][29][30][31][32] For the influence of more basic material properties, such as donor aggregation ability, on film formation kinetics, however, although the conclusions drawn from it would provide important guidance for molecular designs, few studies have touched upon it. Therefore, correlating the aggregation ability of polymer donors with film formation kinetics may lead to efficient devices and some meaningful guidance.…”
Section: Introductionmentioning
confidence: 99%
“…At present, binary all-polymer organic solar cells have achieved a PCE close to 19% . Layer-by-layer (LbL) active layers were prepared by sequential spin-coating technology, which endows the active layers with favorable vertical composition distribution, tunable D/A interfaces and high phase purity in donor or acceptor layer. , Some key scientific issues should be further clarified, such as exciton diffuse distance and exciton utilization efficiency near electrodes. The efficient exciton dissociation in LbL APSCs is a challenge due to the quite limited exciton diffusion distance in organic materials and the relatively small donor/acceptor interface in LbL devices. Some smart strategies of enhancing LbL exciton dissociation focus on increasing the interface of donor layer and acceptor layer, such as enlarging component interdiffusion between donor and acceptor layers by solvent additive, introducing dissociation strengthening layer (DSL) or employing donor incorporation into acceptor layer (DIA) strategy. Wang et al developed a diluted heterojunctions strategy in which APSC of diluting PM6 with 1 wt % PY-IT and diluting PY-IT with 1 wt % D18 achieved a high PCE of 19.4% . It is well-known that exciton diffusion distance strongly depends on the exciton lifetime of donors and acceptors, which should be prolonged by increasing the exciton lifetime of donors and acceptors through incorporating efficient triplet materials with long emission lifetime.…”
mentioning
confidence: 99%